2020
DOI: 10.1097/dcr.0000000000001561
|View full text |Cite
|
Sign up to set email alerts
|

How Should the Low Anterior Resection Syndrome Score Be Interpreted?

Abstract: BACKGROUND: Bowel dysfunction after low anterior resection is often assessed by determining the low anterior resection syndrome score. What is unknown, however, is whether this syndrome is already present in the general population and which nonsurgical factors are associated. OBJECTIVE: The purpose of this study was to determine the prevalence of minor and major low anterior resection syndrome in the general Dutch population and which other factors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…A Danish study on a random sample of 3440 adult citizens from the general population demonstrated that 12–18 per cent of the adult female and 10–11 per cent of the adult male population suffered from symptoms corresponding to major LARS, and the symptoms were associated with unspecified physical disease 33 . A similar prevalence of 12 per cent was found in a general Dutch population, whereas the authors reported a prevalence of symptoms of major LARS at 24 per cent among individuals with diabetes 34 . Similar higher frequencies of small and large intestinal symptoms in individuals with T2D were reported in two reviews 35 , 36 .…”
Section: Discussionsupporting
confidence: 66%
“…A Danish study on a random sample of 3440 adult citizens from the general population demonstrated that 12–18 per cent of the adult female and 10–11 per cent of the adult male population suffered from symptoms corresponding to major LARS, and the symptoms were associated with unspecified physical disease 33 . A similar prevalence of 12 per cent was found in a general Dutch population, whereas the authors reported a prevalence of symptoms of major LARS at 24 per cent among individuals with diabetes 34 . Similar higher frequencies of small and large intestinal symptoms in individuals with T2D were reported in two reviews 35 , 36 .…”
Section: Discussionsupporting
confidence: 66%
“…It is known that after low anterior resection patients can develop LARS, and constipation or FI belong to the most typical symptoms of LARS [23][24][25]. As shown recently, LARS can also be present in the general population [26]. Nevertheless, patients from our study experience Major LARS significantly more often than controls.…”
Section: Discussionsupporting
confidence: 41%
“…With this study, researchers were unable to establish the direct causes of the suboptimal postoperative outcomes regarding patients' bowel functions. The defecatory disorders could already have existed before the patients developed DIE, because such disorders also occur in the 'healthy' population [26]. The causes could have developed or could have become progressively worse along with the growth of endometriosis.…”
Section: Limitationsmentioning
confidence: 99%
“…The LARS score has been proven to be highly sensitive for detecting LARS. However, recent studies showed that LARS is also common in the general population and therefore the score lacks specificity [ 17 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The items used in this questionnaire are as follows: incontinence for flatus, incontinence for liquid stools, frequency of bowel movements, clustering of stools and urgency. Adding item score values results in classification of LARS severity into three groups: 'no LARS' (0-20), 'minor LARS' (21)(22)(23)(24)(25)(26)(27)(28)(29) and 'major LARS' (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). This questionnaire has been validated to evaluate LARS after RC surgery and translated into different languages and normative data have been published [17].…”
Section: Lars Questionnairementioning
confidence: 99%